Plasma cytomegalovirus DNA load predicts outcomes in liver transplant recipients. Issue 1 (3rd November 2020) - Hung, Hao‐Chien; Hsu, Po‐Jung; Lee, Jin‐Chiao; Wang, Yu‐Chao; Cheng, Chih‐Hsien; Wu, Tsung‐Han; Wu, Ting‐Jung; Chou, Hong‐Shiue; Chan, Kun‐Ming; Lee, Wei‐Chen; Lee, Chen‐Fang
Abstract: Objective: Cytomegalovirus (CMV) infection has a significant negative impact on liver transplant (LT) recipients. We aimed to evaluate the efficacy of real‐time DNA quantitative polymerase chain reaction (qPCR) in the early detection of CMV and predicting post‐transplant outcomes. Materials and Methods: This was a retrospective study that enrolled a total of 49 adult LT recipients between December 2016 and October 2019. Serial CMV qPCR were tested weekly. We used operating characteristic curve analysis to quantify qPCR replication numbers to decide the optimal threshold to predict posttransplant complications and overall survival. Results: The optimal cut‐off value of 180 copies/ml (=164 IU/ml) was determined. We had 40 patients in the low qPCR group (<180 copies/ml) and nine patients in the high qPCR group (≥180 copies/ml). Higher qPCR was associated with more severe CMV disease, early allograft dysfunction, major posttransplant complications, longer ICU stays, and lower 2‐year overall survival (OS; all p < .05). In the univariate logistic regression model, persistent DNAemia ≥ 4 weeks after anti‐CMV treatment, coexisted bacterial and/or fungal infection, and high CMV qPCR ≥ 180 copies/ml with p < .100. High CMV qPCR ≥ 180 copies/ml ( p = .016; hazard ratio [HR] = 19.5; 95% confidence interval [CI] = 1.73–219.49) remained to be the only independent risk factors for major complication by the multivariate analysis. The overall 2‐year OS rates were 92.5% and 66.7% in the low and the high qPCR group, respectively ( p = .030). Conclusion: Our findings support evidence that qPCR is effective in detecting CMV infection provides an objective perspective in predicting posttransplant outcomes. High plasma CMV DNA load (defined as CMV qPCR ≥ 180 copies/ml or 164 IU/ml) not only indicates a hazard in developing major posttransplant complications but also associates with prolonged and refractory treatment courses. Abstract : We described that high DNA replication (164 IU/ml) is an indicator of developing major postliver transplant complications. Implementing preemptive treatment for this high‐risk group is mandatory to improve outcomes after liver transplantation.